The prevalence of peripheral neuropathy severe enough to cause a loss of protective sensation in a population‐based sample of people with known and newly detected diabetes in Barbados: a cross‐sectional study. Issue 12 (18th June 2019) - Adams, O. P.; Herbert, J. R.; Howitt, C.; Unwin, N.
Abstract: Aims: To determine the prevalence and potential risk factors for diabetic peripheral neuropathy with a loss of protective sensation in Barbados. Methods: A representative population sample aged > 25 years with previously diagnosed diabetes or a fasting blood glucose ≥ 7 mmol/l or HbA1c ≥ 48 mmol/mol (6.5%) was tested by 10 g monofilament at four plantar sites per foot and a 28 Hz tuning fork and neurothesiometer at the hallux. Data were adjusted to the age structure of people with diabetes in Barbados. Multivariable logistic regression assessed associations with peripheral neuropathy with a loss of protective sensation. Results: Of 236 participants [74% response rate, 33% men, 91% black, median age 58.6 years, mean BMI 30.1 kg/m 2, mean HbA1c 54 mmol/mol (7.1%)], 51% had previously diagnosed diabetes. Foot examination demonstrated that 25.8% (95% CI 20.2 to 31.5) had at least one insensate site with monofilament testing, 14.8% (95% CI 10.2 to 19.4) had an abnormal tuning fork test and 10.9% (95% CI 6.9 to 14.9) had a vibration perception threshold > 25 V. Peripheral neuropathy with a loss of protective sensation prevalence was 28.5% (95% CI 22.7 to 34.4) as indicated by monofilament with ≥ 1 insensate site and/or vibration perception threshold > 25 V. With previously diagnosed diabetes the prevalence was 36.4% (95% CI 27.7 to 45.2) with 98.4% of cases identified by monofilament testing. Increasing age, previously diagnosed diabetes, male sex and abdominal obesity were independently associated with peripheral neuropathy with a loss of protective sensation. Conclusions: Over a third of people with previously diagnosed diabetes had evidence of peripheral neuropathy with a loss of protective sensation. Monofilament testing alone may be adequate to rule out peripheral neuropathy with a loss of protective sensation. Monofilament and neurothesiometer stimuli are reproducible but dependent on participant response. What's new?: In Barbados, foot problems account for 89% of diabetes‐related hospital admissions, but in primary care only 41% had a foot examination over a 2‐year period. Peripheral neuropathy prevalence in a predominantly African descent Caribbean population with diabetes is unknown. In people with known and newly diagnosed diabetes, the prevalence of peripheral neuropathy with a loss of protective sensation was 28.5% (95% CI 22.7 to 34.4) as indicated by monofilament testing with ≥ 1 insensate site and/or vibration perception threshold > 25 V. Monofilament testing alone identified 98% of such cases in people with previously diagnosed diabetes. Monofilament testing alone may be adequate for screening for peripheral neuropathy with a loss of protective sensation.